Diagnosis and treatment of pneumonia in the immunocompromised patient - Nowak, Elżbieta; Ramlau, Rodryg; Ozorowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2001)
Broad diagnostic process is usually required for pneumonia in immunocompromised patient. Protected bronchoscopic or non-bronchoscopic methods (PBS or PBL) should be used for bacterial infection. Detection of galactomanian antigen can be used for Aspergillus, when infection caused by Candida albicans is suspected invasive methods, lung biopsy or videothoracoscopy, are most useful. DFA is used for detection of Pneumocystis carinii infection. PCR-DNA or detection of pp65 antigen are reliable methods for detection of CMV. X-ray picture of the lung can be helpful when treatment is empirical. When infiltrate is localised, common bacterial pulmonary pathogens should be suspected and III generation cephalosporin might be a drug of choice. Fungal infection usually produce nodular infiltrate. When diffuse abnormalities have occurred viral, Chlamydial or Pneumocystis carinii infection can be suspected and combination of trimethoprim/sulfamethoxazol, erythromycin and antiviral drug is used.